Tracing bodies through liminal blends in a mixed reality learning environment. Issue 18 (11th December 2020) - Keifert, Danielle; Lee, Christine; Enyedy, Noel; Dahn, Maggie; Lindberg, Lindsay; Danish, Joshua
ABSTRACT: While research on embodied learning sheds light on the body's role during science learning, there is a lack of understanding of how the body is drawn upon in subsequent learning interactions. We seek to understand how the body supports cognition and learning during and after embodiment. We elaborate upon the liminal blends framework (Enyedy, N., Danish, J. A., & DeLiema, D. (2015). Constructing liminal blends in a collaborative augmented-reality learning environment. International Journal of Computer-Supported Collaborative Learning, 10 (1), 7–34.) to understand how many resources are taken up, blended together, and progressively refined towards canonical scientific understanding. By tracing the body, we demonstrate that embodied experiences are never 'erased.' Instead, although students find ways to articulate understanding that do not require movement, they nonetheless derive meaning from prior embodied activity. Young children exceed expected grade level understanding in part because their capability as embodied reasoners is privileged for learning. In addition to expanding liminal blends theory, we suggest implications for designing technology-enhanced environments and science learning. Across all audiences, findings suggest the importance of privileging an array of sensemaking resources often excluded from classrooms, and the importance of students mapping multiple representational forms to develop conceptual understanding of science phenomena